Exploring the Antibacterial Potential of Platymiscium pinnatum - Mora-Estupiñan, Daniela Alejandra; Chaves-Bedoya, Giovanni; Ortiz Rojas, Luz Yineth (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Antibiotic resistance is a growing concern worldwide, necessitating the exploration of alternative antimicrobial agents. Platymiscium pinnatum (Jacq), a tree belonging to the Fabaceae family, has traditionally held medicinal value, especially in the form of leaf infusions for treating skin and eye infections. This study delves into the antibacterial potential of the ethanolic extract obtained from the bark of P. pinnatum. Using the established Kirby-Bauer agar disk diffusion method, the antibacterial activity of the extract was assessed against both Gram-positive and Gram-negative bacteria. Results indicated a pronounced inhibitory effect on several Gram-positive strains, with Staphylococcus aureus demonstrating the highest susceptibility. This signifies the potential of the extract as a therapeutic agent against infections caused by Gram-positive bacteria. On the contrary, the bioactivity of the extract was comparatively limited against prominent Gram-negative strains, such as E. coli and Pseudomonas aeruginosa. The differential activity between Gram-positive and Gram-negative bacteria could provide insights into the mode of action or specific compounds within the extract. The distinctive antibacterial properties of the P. pinnatum bark extract highlight its potential as a source for developing novel antimicrobial agents. These findings pave the way for further phytochemical analyses and studies to understand the specific bioactive components responsible for the observed effects.